Sosialisasi Edukasi Risiko Bahaya Pada Pekerja Pengelasan di CV. Duta Makmur Abadi - Juwono Wardana Pratama Putra; Moch Sahri; Muhammad Yasir Roja’I Abdilah; Ulfatun Nadiyah Putri; Muslikha Nourma Romadhoni (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
Promotion of OSH culture in the workplace is an activity or activities planned and aimed at improving the safety and health of workers and increasing company productivity whose activities are in the form of training/training, visual management in each work area (safety boards, safety signs, posters, banners, slogans), safety meetings (P2K3 meetings, safety induction, safety briefings), emergency response simulations, both informative, persuasive and emotional messages. One of the CV workers. Duta Makmur Abadi complained when we were interviewed that the worker often experienced shortness of breath, got splashes of gram welding in the eyes, and had watery eyes. Therefore, we socialize regarding the potential hazards that occur in welding workers so that workers are aware of potential hazards. Before and after socialization, the workers are given pre and post tests. These questions are used to find out whether workers understand OSH material about the dangers of welding and from these results workers' knowledge increases from 70 to 90 by 29%. And the social activities of the staff at CV Duta Makmur Abadi were declared successful based on the results of the questions before and after the test.